KAIP ĮMANOMAS ĮNIRTINGAS ŽALIŲ BESPALVIŲ IDĖJŲ MIEGAS? - Sabolius, Kristupas (Problems / Problemos, 2012)
The article is based on the sentence composed by Noam Chomsky: "Colorless green ideas sleep furiously". Although a phenomenon referred to by this grammatically correct, but logically contradictory phrase is not to be found in the empirical field, it can stimulate a certain perspective of experience in the field of imagination. The cultivation of this oxymoronic unity of opposites serves for a better understanding of the latent function of imagination. Based on the insights of Anaximander, Beckett, Stoics, Descartes, British empiricists, Husserl, and Sartre, this sentence is reconsidered as a phenomenological exercise facilitating the dynamism of the activity and passivity of consciousness as well as turning the logical contradiction into the principle of orientation of change.